Bukan sekadar bertahan: Menavigasi narasi ketahanan psikososial suku Kajang di tengah modernisasi yang hegemonik - Anugrah, Muhammad Rafli; Musa, Nur Inayah; Arifin, Nurly Fatin Ramadhani; Afandi, Ichlas Nanang (Jurnal Psikologi Ulayat, 2025)
This study examines the psychosocial resilience narratives of the indigenous Kajang community as a collective response to the hegemony of modernization. Using a multi-layered phenomenological approach, data were gathered through participatory observation, in-depth interviews, and literature review. The findings reveal that resilience is rooted in collective knowledge of the first Ammatoa, who foresaw modernization’s impact. Resilience manifests across three interwoven layers: personal (inner meaning-making and inner state), spiritual (belief in the sacredness of ancestral land), and communal (shared identity and values grounded in the Tallasa Kamase-Masea philosophy). The integration of these three layers serves as a reflective element that strengthens the Kajang community’s awareness and efforts to preserve their cultural heritage by decelerating value shifts amid the pressures of modernization. Globally, this research can open up opportunities or generate findings based on decolonizing psychology, allowing psychological concepts to genuinely emerge from the unique context of a given culture.